Pemetaan Masalah Pribadi Peserta Didik Menggunakan Aplikasi DCM (Daftar Cek Masalah) - Diana Lating, Ainun; Mahaly, Sawal; Farhan, Muhammad (At-Taujih : Bimbingan dan Konseling Islam, 2026)
This study is motivated by the importance of understanding students’ personal problems that may affect their development and academic success. Various problems experienced by students, both internal and external, need to be systematically identified in order to provide appropriate guidance and counseling services. This study aims to map students’ personal problems using the Problem Checklist Application (Daftar Cek Masalah/DCM) to obtain a comprehensive overview of students’ conditions. This research employed a quantitative approach with a descriptive design. The subjects consisted of 120 students of SMA Negeri 44 Maluku Tengah selected through total sampling technique. Data were collected using the Student Needs Questionnaire, which covers various aspects of student problems. The data were analyzed using a computerized program to obtain the distribution and percentage of students’ problems. The results showed that a total of 772 problems were identified. Health aspects were the most dominant, accounting for 32.64%, followed by recreation and hobbies (19.69%), economic conditions (17.62%), family life (15.8%), and religion and moral aspects (14.25%). These findings indicate that both physical and psychological health significantly influence students’ lives and learning processes   Keywords: Personal Problem, Problem Checklist